Peran Pendidikan Islam dalam Membentuk Kesadaran Hukum Syariah di Masyarakat Muslim - Dika Ramadhani Fauzan; Reza Ananta Putra (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2024)
This research examines how Islamic education plays a role in raising awareness of sharia law among Muslim communities. Using a qualitative approach, this study explores the methods of teaching Islamic law in Islamic boarding schools, madrasas, and Islamic universities. The results show that Islamic education based on the understanding of the Qur'an and Hadith can increase awareness of sharia law and compliance with Islamic rules in daily life.